2005
DOI: 10.1093/jxb/erj029
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity and growth temperature: understanding interspecific variability

Abstract: The subject of this review is the impact of long-term changes in temperature on plant growth and its underlying components. The discussion highlights the extent to which thermal acclimation of metabolism is intrinsically linked to the plasticity of a range of biochemical and morphological traits. The fact that there is often a trade-off between temperature-mediated changes in net assimilation rates (NAR) and biomass allocation [in particular the specific leaf area (SLA)] when plants are grown at different temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
169
2
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(193 citation statements)
references
References 71 publications
8
169
2
7
Order By: Relevance
“…The decrease in SLA with increasing altitude can be realized through increases in leaf density and leaf thickness (Körner 2003;Atkin et al 2006;Poorter et al 2009). Both increased density and increased thickness are often observed in deciduous herbs; the former through limited cell expansion leading to smaller cells and more cells per unit leaf volume, the latter through increases in the number of palisade parenchyma layers (Körner 2003;Poorter et al 2009).…”
Section: Phenotypic Plasticitymentioning
confidence: 99%
“…The decrease in SLA with increasing altitude can be realized through increases in leaf density and leaf thickness (Körner 2003;Atkin et al 2006;Poorter et al 2009). Both increased density and increased thickness are often observed in deciduous herbs; the former through limited cell expansion leading to smaller cells and more cells per unit leaf volume, the latter through increases in the number of palisade parenchyma layers (Körner 2003;Poorter et al 2009).…”
Section: Phenotypic Plasticitymentioning
confidence: 99%
“…We know little about how metabolism and growth adjust to a fluctuating temperature regime, which features of the regime they respond to, and whether they always respond to temperature in the same way. Temperature affects almost all cellular and physiological processes, with the effect depending on the process (Larcher, 1995;Atkin and Tjoelker, 2003;Atkin et al, 2006). Photochemical processes are effectively temperature-insensitive, diffusion-based processes that vary as a function of the change in the absolute temperature (;0.03-fold per 10°C change in the physiological range), enzyme activities typically decrease two-to threefold for each 10°C decrease in temperature (often termed the Q 10 ; Larcher, 1995), and membrane-based processes are additionally affected by physical changes in the properties of lipids.…”
Section: Introductionmentioning
confidence: 99%
“…3c and 6a). Third, high NAR was suggested to be affected by high R s and low T a (Table 3), as previous studies have also shown that high temperatures (23-28°C) decrease NAR through plant respiration loss (Atkin et al, 2006). In several woody plants, high SLA and LAR enhance RGR because they confer high light interception and carbon gain per unit mass invested in leaves (Lambers and Poorter, 1992;Poorter and Remkes, 1990;Reich et al, 1992Reich et al, , 1998Walters et al, 1993).…”
Section: Reaction Of Seedling Growth To the Environmentmentioning
confidence: 88%